ANALISIS STRUKTUR MODAL, PERTUMBUHAN DAN GCG TERHADAP KINEJA PERUSAHAAN PADA INDUSTRI Consumer Goods YANG TERDAFTAR DI BEI - Saraswati, Wiwik; Rama Pramudia, Dimas; Nazila Hakil Udhma, Ziad (Fakultas Ekonomi Universitas Balikpapan, 2023)
This research aims to determine how the influence of capital structure (Dunnas et al., 2020), company growth (Ismiyanti, 2022), and the board of commissioners (Ayu et al., 2019) on company value (Kolamban et al., 2020) on(Kolamban et al., 2020)The IDX used 23 samples from 53 populations. The results of this study show that the capital structure has a significant positive effect on the value of the company, this certainly makes the efficiency of using the capital structure on maximum debt will have a positive impact on the funding of a company. The growth of the company has no effect on the value of the company. The greater the growth rate of the company, the higher the costs needed to manage the company's operational activities. The company will focus its funds more on the company's growth needs than shareholder welfare.